Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1210/jc.2013-3958
|View full text |Cite|
|
Sign up to set email alerts
|

Corrigenda

Abstract: Context:The role and importance of circulating sclerostin is poorly understood. High bone mass (HBM) caused by activating LRP5 mutations has been reported to be associated with increased plasma sclerostin concentrations; whether the same applies to HBM due to other causes is unknown.Objective:Our objective was to determine circulating sclerostin concentrations in HBM.Design and Participants:In this case-control study, 406 HBM index cases were identified by screening dual-energy x-ray absorptiometry (DXA) datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…NPR3 may be the target gene regulated by rs9292469, as our human osteoblast eQTL data do not support an alternative target, and we and others have shown Npr3 expression in the mouse skeleton [ 48 ]. Previous findings in our unexplained HBM population have shown that although adult height is no different from controls, trabeculae are thicker increasing trabecular density [ 57 , 58 ], possibly recapitulating observations in Npr3 -mutant mice [ 47 , 49 ]. Our previous analyses suggested unexplained HBM protects against age-associated declines in trabecular BMD [ 57 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…NPR3 may be the target gene regulated by rs9292469, as our human osteoblast eQTL data do not support an alternative target, and we and others have shown Npr3 expression in the mouse skeleton [ 48 ]. Previous findings in our unexplained HBM population have shown that although adult height is no different from controls, trabeculae are thicker increasing trabecular density [ 57 , 58 ], possibly recapitulating observations in Npr3 -mutant mice [ 47 , 49 ]. Our previous analyses suggested unexplained HBM protects against age-associated declines in trabecular BMD [ 57 ].…”
Section: Discussionsupporting
confidence: 83%
“…Spon1 knockout mice have a skeletal phenotype consistent with HBM, with Spon1 −/− mice at 6 months age having 60% higher bone volume, bone volume/total volume, cortical area and trabecular number with reduced trabecular spacing [ 59 ]. Increased trabecular density and reduced endosteal expansion is seen in human HBM [ 57 , 58 ]. Serum CTX-1 and TRAP levels are normal in Spon1 −/− mice; however, TGF-β1 levels are reduced compared with WT mice, whilst SMAD 1/5 activation is enhanced in both osteoblasts and chondrocytes [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Szulc et al [27] found a similar relationship in male patients with normal renal function, and this association has been reported in post-menopausal women without CKD [28]. Moreover, individuals with genetically high bone mass have higher serum sclerostin levels than controls [29]. This could be in apparent contradiction with the known impact of sclerostin on post-menopausal osteoporosis [30].…”
Section: Discussionmentioning
confidence: 98%
“…(26-28) Hence, our patient's hypersclerostinemia could seem paradoxical. In the high-bone-mass disorder due to activating mutations within LRP5 causing increased WNT signalling, (29) circulating SOST levels are normal (29-30) or increased. (31) For our patient, mutation analysis was negative for SOST, LRP5, LRP4, and osteopetrosis genes.…”
Section: V) Discussionmentioning
confidence: 99%